Response of rice (Oryza sativa) to urea form and nitrogen level under transplanted condition - MUTANAL, S M; KUMAR, PRASAD; JOSHI, V R; PRABHAKAR, A S (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during rainy season (kharif) 1992, 1993 and 1994 at Sirsi in Karnataka to study the response of urea fonns and nitrogen levels on grain yield of rice (Oryza sativa L.) under transplanted condition. The experiment consisted of 3 levels of nitrogen and 4 sources of nitrogen and was replicated thrice in factorial randomized block design. Application of nitrogen through nimin-coated urea proved superior than through prilled urea, tar-coated urea and large urea granules. The optimum dose was 75 kg/ha, which recorded higher return compared with 50 and 100 kg/ha.